Why are we not all allergic: basic mechanisms for tolerance development - Halstensen, Trond S (Environmental toxicology and pharmacology, 1997)
Harmless antigens encountered on the mucosal surface are normally tolerated in the sense that they do not induce inflammatory immune responses. Oral tolerance is the type of mucosal immune regulation that prevents inflammatory reactions to food proteins. However, parasites and invasive microorganisms at the mucosal surfaces must be recognised and dealt with in a proper manner. The immune system does so by cross-regulating the response where it either produces IgA to exclude invasion, IgE to fight parasites, or IgG to destroy the invasive organisms. Allergy is an anti-parasitic reaction to a misinterpreted but harmless antigen. This lack of tolerance induction is influenced by genetic factors controlling the amount of interleukin (IL)-4 produced initially in the immune response. IL-4 directs B-cells to produce IgE, induces naive T-cells to become IL-4 producing T-helper cells (Th2 cells) and prevent other T-cells from entering into the IFN-γ-producing Th1 pathway. Long lasting Th2 clones lose their IL-12 responsiveness and can no longer be induced to produce IFN-γ thus they are locked in an allergy inducing Th2 phenotype. Environmental factors play on the genetic background and influence the outcome of the immune response. Mucosal tolerance depends on an intact mucosal surface, is influenced by the age of the subject, and can be manipulated through antigen dose and place of entry. Immune-manipulating therapy may be more successful in primary than in secondary prevention of allergy.